Intraneural perineurioma of the brachial plexus - (:unkn) unknown (My University, 2010)
İntranöral perinöroma (İP) iğsi perinöral hücrelerin ortalarında schwan hücreleri bulunarak veya bulunmayarak oluşturdukları soğan benzeri histopatolojik yapı ile karakterize nadir görülen ve yavaş ilerleyen bir hastalıktır. Tanısı büyük oranda histolojik bulgulara ve immunhistokimyasal profile dayanır. İP diğer yumuşak doku tümörlerinden ayrılmasında sitogenetik ve moleküler genetik çalışmalar önemli rol oynar.

Intraneural perineurioma(IP) is a rare and slowly progressing disease which is characterized by spindled perineurial cells, arranged in pseudo-onion bulb whorls around one or more centrally situated Schwann cells. Diagnosis of the disease is based mainly on histologic findings and immunohistochemical profile. Although cytogenetic and molecular genetic studies are of limited value, they may play an important role in the differential diagnosis of the IP, with many other overlapping soft tissue tumors.
Brakiyal pleksusun intranöral perinöroması
Keywords: Genel ve Dahili Tıp